Anthropogenic changes in Lake Korttajärvi from the 17th century to the present - Kehusmaa, Karoliina (fi=Turun yliopisto|en=University of Turku|, 2017)
Human activities have influenced most European waterbodies. These anthropogenic changes often started intensifying in the 19th century with the onset of industrialisation and modern agriculture. Lake sediments are excellent records of these past changes. Certain conditions also allow the formation of annual laminations, called varves, in the sediment. These can be inexpensively and easily used to establish a high-resolution chronology. Anthropogenic changes from AD 1600 to AD 2010 were studied from Lake Korttajärvi, a small, varved lake in central Finland, using different physical, chemical and biological proxies. Magnetic susceptibility was measured to infer the past intensity of erosion into the lake. The sediment core, dated with varve counting, was divided into subsamples covering 10 years. From each subsample, the sediment total phosphorus and three sediment phosphorus fractions were determined. Diatoms were also identified from each subsample and their species turnover was examined statistically. In addition, the diatom assemblages were used to quantitatively reconstruct the past total phosphorus and electrical conductivity values of the lake water. The samples of AD 1600-1770 seemingly reflected slash-and-burn cultivation around Lake Korttajärvi. A constant diatom species turnover started in the 1770s simultaneously with changes in the physical and chemical properties of the sediment, suggesting the onset of notable anthropogenic influence on the lake. After AD 1770, the sediment properties reflect the increasing land use around the lake. The most affected phase was AD 1960-1990, when municipal waste waters were discharged into the lake. The 21st century samples seemed to reflect a slight recovery.